Digital Accounting Transformation as a Driver of Sustainable Business Model Innovation through Digital Ecosystems in Start-ups in Indonesia - Judijanto, Loso; Melatnebar, Benyamen Minggus (Westscience Press, 2025)
This study explores the role of digital accounting transformation and digital ecosystems in driving sustainable business model innovation (SBMI) within Indonesian start-ups. Using a quantitative analysis with 85 samples, data were collected through a Likert scale survey and analyzed using SPSS Version 26. The results reveal that digital accounting transformation significantly influences SBMI, with a path coefficient of 0.52. Additionally, digital ecosystems were found to have a moderate positive effect on SBMI (path coefficient: 0.41). The study also identifies a mediating role of digital ecosystems, with an indirect effect of 0.26, showing that digital ecosystems amplify the impact of digital accounting transformation on SBMI. These findings underscore the importance of integrating digital technologies and ecosystems to foster innovation and sustainability in start-up businesses. The study provides practical insights for entrepreneurs and policymakers, highlighting the necessity of adopting digital tools and fostering ecosystem collaboration to achieve sustainable business growth.